Integrated Reporting in Healthcare Entities in the Light of Stakeholder Theory - Jaskólska, Apolonia; Auguścik, Adriana; Cygańska, Małgorzata (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: The article identifies the role of integrated reporting in healthcare entities implementing a sustainable development policy in the light of stakeholder theory.Research Design & Methods: The research was based on literature published in Polish as well as English concerning the main stakeholders of healthcare entities – patients, citizens, hospital staff and the government. The use of integrated reporting in selected countries was examined.Findings: The research has shown that reporting determines the relationship between the  organisation’s business model, its strategy, and the independent evaluation of results.Implications / Recommendations: Managers at healthcare entities that have better relationships with stakeholders are more aware and involved in reporting results in order to meet their information needs. Integrated reporting is a key information exchange tool, one that is useful for strengthening relationships with stakeholders, so it is imperative to include all stakeholder groups to obtain the best possible results.Contribution: The article outlines the legitimacy of using integrated reporting, treated as an innovative instrument of communication between the business entity and its stakeholders.